The relationships between emerging adults self-efficacy and motivation levels and physical activity: a cross-sectional study based on the self-determination theory - Tao, Yuexian; Xu, Tao; Wang, Xin; Liu, Chengyi; Wu, Yinyin; Liu, Mingyue; Xiao, Ting; Qiu, Xinze (Frontiers in Psychology, 2024)
The study aims to examine the associations between exercise self-efficacy, motivation, physical activity, and body composition among emerging adults.Methods: Structural Equation Modeling is a statistical technique that allows for simultaneous examination of complex relationships among multiple variables. It enables researchers to assess both direct and indirect effects within a single model, providing a comprehensive understanding of the underlying mechanisms at play. The PLS-SEM analysis with bootstrapping in Smart PLS 3 showed important path coefficients and t-values for the relationships that were thought to exist in this study. Significance was determined using a threshold of p < 0.05.